Dissection of the Role of VIMP in Endoplasmic Reticulum-Associated Degradation of CFTRΔF508 - Hou, Xia (Sci Rep, 2018)
Endoplasmic reticulum (ER)-associated protein degradation (ERAD) is an important quality control mechanism that eliminates misfolded proteins from the ER. The Derlin-1/VCP/VIMP protein complex plays an essential role in ERAD. Although the roles of Derlin-1 and VCP are relatively clear, the functional activity of VIMP in ERAD remains to be understood. Here we investigate the role of VIMP in the degradation of CFTRΔF508, a cystic fibrosis transmembrane conductance regulator (CFTR) mutant known to be a substrate of ERAD. Overexpression of VIMP markedly enhances the degradation of CFTRΔF508, whereas knockdown of VIMP increases its half-life. We demonstrate that VIMP is associated with CFTRΔF508 and the RNF5 E3 ubiquitin ligase (also known as RMA1). Thus, VIMP not only forms a complex with Derlin-1 and VCP, but may also participate in recruiting substrates and E3 ubiquitin ligases. We further show that blocking CFTRΔF508 degradation by knockdown of VIMP substantially augments the effect of VX809, a drug that allows a fraction of CFTRΔF508 to fold properly and mobilize from ER to cell surface for normal functioning. This study provides insight into the role of VIMP in ERAD and presents a potential target for the treatment of cystic fibrosis patients carrying the CFTRΔF508 mutation.